Deciphering the interplay between SETD2 mediated H3K36me3 and RNA N6-methyladenosine in clear cell renal cell carcinoma (ccRCC) - Shafiq Shaikh; Xia Zhao; Ryan T. Wagner; Xiaoyu Pan; Ryan A. Hlady; Liguo Wang; Thai H. Ho; Keith D. Robertson (Epigenetics)
RNA N6-methyladenosine (m6A) plays diverse roles in RNA metabolism and its deregulation contributes to tumor initiation and progression. Clear cell renal cell carcinoma (ccRCC) is characterized by near ubiquitous loss of VHL followed by mutations in epigenetic regulators PBRM1, SETD2, and BAP1. Mutations in SETD2, a histone H3 lysine 36 trimethylase (H3K36me3), are associated with reduced survival, greater metastatic propensity, and metabolic reprogramming. While m6A and H3K36me3 deregulation are separately implicated in renal tumorigenesis, H3K36me3 may participate directly in m6A targeting, but the m6A-H3K36me3 interplay has not been investigated in the context of ccRCC. Using RCC-relevant SETD2 isogenic knockout and rescue cell line models, we demonstrate a dynamic redistribution of m6A in the SETD2 depleted transcriptome, with a subset of transcripts involved in metabolic reprogramming demonstrating SETD2 dependent m6A and expression level changes. Using a panel of six histone modifications we show that m6A redistributes to regions enriched in gained active enhancers upon SETD2 inactivation. Finally, we demonstrate a reversal of transcriptomic programs involved in SETD2 loss mediated metabolic reprogramming, and reduced cell viability through pharmacologic inhibition or genetic ablation of m6A writer METTL3 specific to SETD2 deficient cells. Thus, targeting m6A may represent a novel therapeutic vulnerability in SETD2 mutant ccRCC.